Рівні правової культури офіцерського складу Збройних Сил України (за ре зультатами конкретно-соціологічного дослідження) - Скуріхін, Сергій Миколайович; Скурихин, Сергей Николаевич; Skurihin, Sergej (Одеса : Юрид. л-ра, 2012)
In this article the analysis of results of concrete-sociological research of legal culture of officers of Armed forces of Ukraine was conducted. It was revealed that the general level of legal culture of officers is low enough. The conclusion on necessity of perfection of system of legal education, search and introduction of new forms, means and methods of legal-educational work was drawn. Herewith special value has legal informing of officers.
Скуріхін С. М. Рівні правової культури офіцерського складу Збройних Сил України (за ре зультатами конкретно-соціологічного дослідження) / С. М. Скуріхін // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 280-287.
Keywords: правові цінності офіцерського складу; правова поведінка офіцерів; правова інформованість офіцерів; рівні правової культури офіцерів; правовые ценности офицерского состава; правовое поведение офицеров; правовая информированность офицеров; уровни правовой культуры офицеров; legal values of officers; legal behavior of officers; legal awareness of officers; levels of legal culture of officers